Pengaruh Kebijakan Dividen dan Pengungkapan Laporan Keberlanjutan Terhadap Nilai Perusahaan pada Sektor Pertambangan - Maya Eka Yuriana (Fakultas Ekonomi dan Bisnis, 2026)
This study aims to examine and analyze the effect of dividend policy and sustainability report disclosure on firm value in mining sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. This study employs a quantitative causal approach using multiple linear regression analysis on 31 observations obtained through purposive sampling. Firm value is measured using Tobin's Q. Dividend policy is measured by the Dividend Payout Ratio (DPR), while sustainability report disclosure is measured using the Sustainability Report Disclosure Index (SRDI). Profitability, measured by Return on Assets (ROA), is included as a control variable. The results indicate that dividend policy has no significant effect on firm value, while sustainability report disclosure has a positive and significant effect on firm value. Profitability as a control variable also has a positive and significant effect on firm value. Simultaneously, dividend policy, sustainability report disclosure, and profitability significantly affect firm value. These findings suggest that investors place greater emphasis on sustainability disclosure and corporate profitability than on dividend distribution in assessing the value of mining companies.
Finalisasi 20 Juli 2026_Yudi
Keywords: dividend policy; sustainability report disclosure; firm value; mining sector